Hypermethylated PAX1 and ZNF582 genes in the tissue sample are associated with aggressive progression of oral squamous cell carcinoma. (3rd June 2020) - Sun, Rui; Juan, Yi‐Chen; Su, Yee‐Fun; Zhang, Wen‐Bo; Yu, Yao; Yang, Hong‐Yu; Yu, Guang‐Yan; Peng, Xin
Abstract: Background: DNA methylation of paired box gene 1 (PAX1) and zinc finger 582 (ZNF582) is promising cancer biomarkers for oral squamous cell carcinoma detection. This study aims to investigate the correlation between PAX1 or ZNF582 methylation and the progression of oral squamous cell carcinoma (OSCC). Materials and Methods: A total of 135 OSCC cases from Peking University School and Hospital of Stomatology were enrolled in this study. Tissue specimens were collected from the lesion site and corresponding adjacent normal site. The methylation level of these two genes was evaluated in primary and recurrent OSCC group. Results: Hypermethylation of PAX1 or ZNF582 was observed in lesion sites among primary and recurrent OSCC cases. In the lesion site of primary cases, promoter methylation was observed in T3/T4 ( PAX1 : P = .02; ZNF582 : P = .01), stage III/IV ( PAX1 : P = .03; ZNF582 : P = .01), and bone invasion cases ( PAX1 : P = .02; ZNF582 : P = .047). In the subgroup analysis, the correlation between hypermethylation and OSCC severity remains significant with exposure to smoking/alcohol consumption. Conclusions: Hypermethylated PAX1 and ZNF582 can sufficiently act as biomarkers to reflect the severity or progression of OSCC.